N. F. S. Grundtvigs trinitariske folkekirketeologi i nordisk kontekst - Iversen, Hans (Grundtvig-studier, 2012)
N.F.S. Grundtvigs trinitariske folkekirketeologi i nordisk kontekst[Trinitarian Folk Church Ecclesiology by N. F. S. Grundtvig in a Nordic Context]By Hans Raun Iversen In the theological writings of N. F. S. Grundtvig we find a unique balance and interaction between what Grundtvig labels the first and the second creation (creation of heaven and earth and creation of salvation) by the one and same Trinitarian God. This makes Grundtvig outstanding in terms of the significance of the theology of creation in his profoundly elaborated Trinitarian theology. On this background Grundtvig is also offering a Trinitarian balanced ecclesiological understanding of the church which is decisive but still only rarely found in the Nordic Folk Churches. In the same breath Grundtvig offers a comprehensive contribution to a Trinitarian theology of participation in the communication of the Trinity where there is a living interaction not only between the primary theology found in God’s own living words in creation and in liturgy, but also between this primary theology and the secondary theological reflection of the two forms of primary theology